Long-Term Health-Related Quality of Life of Surgically Treated Pituitary Adenoma Patients: A Descriptive Study. (31st December 2012) - Raappana, A.; Pirilä, T.; Ebeling, T.; Salmela, P.; Sintonen, H.; Koivukangas, J.
Abstract : Context . The literature concerning the health-related quality of life (HRQoL) of patients with surgically treated PA is controversial. Objective . To describe the long-term HRQoL of surgically treated patients in all PA classes. Design and subjects . The 15D, a generic HRQoL instrument producing a 15-dimensional profile and a single 15D index score (a difference ≥0.03 on a 0-1 scale is considered clinically important), was used to assess the HRQoL of a 13-year surgical cohort of PA patients in Northern Finland. Results and Conclusion . Nighty-eight eligible consecutive patients with surgically treated PA were studied at an average of 6.3 years after their latest pituitary operation. The average postoperative 15D profiles in patients with non-functioning PA and in acromegalics without GH-suppressive medical treatment were similar to those of the age-standardized general population. However, after this rather long followup, the mean 15D score and the number of statistically significant 15D dimension impairments, compared with those of their reference population, were 0.11 and 9/15, 0.10 and 3/15, and 0.08 and 7/15 for Cushing's disease, acromegalics needing somatostatin analog, and prolactinoma patients, respectively. Hypopituitarism with replacement medication was not associated with impaired HRQoL. The somatostatin-analog-associated HRQoL finding warrants further clinical research.